Membangun Kepercayaan Konsumen Untuk Meningkatkan Wom Pada E-Commerce Shopee - Hendra Nurrahman (Universitas PGRI Yogyakarta, 2021)
This study aims to determine building consumer trust to increase WOM on E-Commerce Shopee (Case study on UST FE students). In this study, the sample used was UST FE students as many as 96 respondents. The sampling technique used in this study was simple random sampling. The results of the analysis show that Web Design has a positive effect on Satisfaction with Shopee users on FE UST. The most dominant factor influencing Wom shopee is Trust.Keyword: Shopee, WOM, trustÂ Â